Pathogenicity of isolates of metarhizium anisopliae (metsch.) Sorokin towards the cattle tick boophilus microplus (can.) (Acari: Ixodidae) under laboratory conditions - Monteiro, Antonio Carlos [UNESP] (1998)
The pathogenic activity of Metarhizium anisopliae on Boophilus microplus females was assessed using five fungal isolates. Groups of 8 engorged ticks collected from cattle on free pasture were inoculated by immersion for 5 seconds in a spore suspension containing 2.5 x 108 conidia/ml. The groups were transferred to moist chambers in which they were maintained at 27 ± 1°C for about 15 days, their mortality being determined every 2, or occasionally 3, days. The isolate that produced the best results in this assay was used to inoculate female ticks with spore suspensions containing 0, 7.5 x 105, 7.5 x 106, 7.5 x 107 and 7.5 x 108 conidia/ml, under the same conditions as described above. The pathogenic action of M. anisopliae on engorged females was clearly demonstrated. Isolates E9 and AM were more effective, causing high tick mortality as well as reduced oviposition. The concentration of 7.5 x 108 conidia/ml was the most effective, with the fungus sporulating on 91.1% of the ticks. Mean percent oviposition was highest in the control treatment and lowest in the treatment with 7.5 x 108 conidia/ml.